2015
DOI: 10.1007/s12532-015-0090-6
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale optimization with the primal-dual column generation method

Abstract: The primal-dual column generation method (PDCGM) is a general-purpose column generation technique that relies on the primal-dual interior point method to solve the restricted master problems. The use of this interior point method variant allows to obtain suboptimal and well-centered dual solutions which naturally stabilizes the column generation. As recently presented in the literature, reductions in the number of calls to the oracle and in the CPU times are typically observed when compared to the standard col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 63 publications
(167 reference statements)
0
40
0
Order By: Relevance
“…The CG-based heuristic was coded in C++ and relies on the BP framework of Munari and Gondzio [27] designed for the VRPTW, and the BC algorithm of Munari and Savelsbergh [29] designed for the SDVRPTW. The BP algorithm used to solve VRPTW instance is based on the primal-dual column generation method and relies on interior point solutions to stabilize column and cut generation [22,23]. The BP algorithm is called three times in the first phase of the heuristic, and in the second and third calls, we initialize the master problem with the columns obtained in previous call.…”
Section: Computational Studymentioning
confidence: 99%
“…The CG-based heuristic was coded in C++ and relies on the BP framework of Munari and Gondzio [27] designed for the VRPTW, and the BC algorithm of Munari and Savelsbergh [29] designed for the SDVRPTW. The BP algorithm used to solve VRPTW instance is based on the primal-dual column generation method and relies on interior point solutions to stabilize column and cut generation [22,23]. The BP algorithm is called three times in the first phase of the heuristic, and in the second and third calls, we initialize the master problem with the columns obtained in previous call.…”
Section: Computational Studymentioning
confidence: 99%
“…Stabilization techniques try to overcome these drawbacks by controlling the oscillation of dual solutions, which has been shown to be successful for a variety of problems (Briant et al 2008, Ben Amor et al 2009. We rely on the technique known as the primal-dual column generation method (Gondzio et al 2013, Gondzio et al 2016, which uses a primal-dual interior point algorithm to naturally control the distance between dual solutions. Each RMP is solved by the interior point algorithm within a given optimality tolerance ε > 0 that is dynamically adjusted at each CG iteration according to the relative gap in the CG method.…”
Section: Column Generationmentioning
confidence: 99%
“…We solve the SDP and LP relaxations of the max-k-cut using the interior point method (IPM) of MOSEK [3]. Our computational tests indicated that the default IPM is not efficient so, inspired by the PDCGM solver [19], we considerably modified the IPM to improve the CPA performance. This section discusses the main changes; some of them are also applicable to other solvers.…”
Section: Solving the Relaxationsmentioning
confidence: 99%